Impact of Passive Laboratory Alerts on Navigating Electronic Health Records in Intensive Care Simulations. (May 2018) - Arthurs, Benjamin J.; Mohan, Vishnu; McGrath, Karess; Scholl, Gretchen; Gold, Jeffrey A.
Passive alerts highlighting abnormal results in the electronic health record (EHR) are abundant. However, their impact on EHR use and contribution to alert fatigue remains unknown. We examined the impact of passive laboratory alerts on EHR usability and recognition of patient safety issues during a simulated intensive care unit (ICU) rounding exercise. We performed a post hoc comparison of simulated ICU rounding exercises, comparing performance with and without passive laboratory alerts. Participants (physician trainees and advanced practice providers) reviewed EHRs depicting critically ill patients, which included multiple embedded patient safety issues. We employed eye tracking during chart review to determine the impact of alerts on EHR navigation. 92 simulations were reviewed, 46 with passive alerts activated. Passive alerts were associated with reduced gaze fixations on both normal and abnormal laboratory results. Activation of alerts was also associated with increased time to first fixation on abnormal results and increased saccadic eye movements. Alerts had no impact on either the duration spent reviewing laboratory results or identification of patient safety issues. Activating passive alerts in the EHR was associated with increase scanning behavior, which may explain why reductions in gaze fixations on lab results did not translate into improved efficiency or performance. This may be due to alert fatigue in the form of oversearching.